2019
DOI: 10.1016/j.hrthm.2019.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Cryoballoon pulmonary vein ablation and left atrial appendage closure combined procedure: A long-term follow-up analysis

Abstract: BACKGROUND The combined left atrial appendage closure (LAAC) and cryoenergy pulmonary vein isolation (PVI) procedure has been proven safe and effective in managing stroke in patients with nonvalvular atrial fibrillation (AF), although most data refer to procedures performed using radiofrequency as the main energy source. OBJECTIVE The purpose of this study was to evaluate long-term follow-up of patients with AF undergoing concomitant LAAC and cryoenergy PVI. METHODS Patients undergoing LAAC and cryoballoon PVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Previous studies of LAAC combined with electrophysiological and structural interventions have shown that in the long term 5,6,21 . This was also the case for a combined approach of concomitant LAAC and AF ablation, which was not only feasible and safe, but also substantially reduced stroke and bleeding events as compared to anticipated rates predicted by the CHA 2 DS 2 ‐VASc and HAS‐BLED scores.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies of LAAC combined with electrophysiological and structural interventions have shown that in the long term 5,6,21 . This was also the case for a combined approach of concomitant LAAC and AF ablation, which was not only feasible and safe, but also substantially reduced stroke and bleeding events as compared to anticipated rates predicted by the CHA 2 DS 2 ‐VASc and HAS‐BLED scores.…”
Section: Discussionmentioning
confidence: 83%
“…At a 24 ± 12‐month follow‐up, an 80% freedom from arrhythmias was achieved; a high long‐term complete LAA sealing (92%) was described, with all other patients experiencing a <5‐mm leakage. These results were then confirmed at a longer follow‐up and in a larger patient sample by a second study from the same group . Combined procedure feasibility, safety, and effectiveness regardless of the energy source for PVI (RF or Cryo) and device brand choice was demonstrated with this experience; no evidence of the superiority of an energy source on the other are available to date, leaving the option (and the burden) of the choice to the operator .…”
Section: “Here Comes the Ice”: Cryo‐energy Combined Proceduresmentioning
confidence: 70%
“…In 2016, cryo‐energy instead of RF as an energy source was introduced in the combined procedure by Fassini et al They reported the safety and feasibility of the technique using cryo‐energy delivered through first‐ and second‐generation cryoballoons in a high stroke risk population. In their pilot study, 35 patients were enrolled and underwent cryoballoon PVI alongside WATCHMAN or ACP LAAC; periprocedural reported adverse event rate and procedural time resulted comparable to previous RF CA combined procedure experiences.…”
Section: “Here Comes the Ice”: Cryo‐energy Combined Proceduresmentioning
confidence: 99%
“…Moreover, Fassini et al 17 were the first to report comparable results of the combined procedure, utilizing only CB for ablation in 35 AF patients. Thenceforth, several studies have provided further evidence to support the feasibility of the CB ablation combined procedure, 7,12 showing comparable clinical outcomes with the RF combined procedure 4–6 . The CB ablation combined procedure forms a novel approach for AF management.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2012, combining catheter ablation with left atrial appendage closure (LAAC) has been reported as a promising therapy for patients with AF 4 . Since then, several centers worldwide have reported considerable efficacy and safety of this combined procedure 5–7 . Notably, the presence of prominent acute LAR lesions after the combined procedure has been reported in some studies 8,9 .…”
Section: Introductionmentioning
confidence: 99%